Reliability of Cervical Neural Foramen Stenosis Grading Based on Axial Three-Dimensional Magnetic Resonance Images - Panyaping T. (2023)
Objective: To assess the reliability of cervical neural foramen stenosis (CNFS) grading by using three-dimensional (3D) T1W, 3D T2W, and two-dimensional (2D) T2W images in axial plane. Materials and Methods: The authors enrolled 32 patients between December 2019 and February 2020 who underwent cervical spine magnetic resonance imaging (MRI) with clinical manifestations of cervical spondylosis. Two blinded radiologists interpreted the axial 3D T1W TSE, 3D T2W TSE, and 2D T2W TSE images using a 4-point visual scale for CNFS grading in all cervical levels. Intra-observer agreement of CNFS grading on the three imaging pulse sequences for each observer and inter-observer agreement between both observers were analyzed using intra-class correlation coefficient (ICC). Results: Three hundred eighty-four neural foramina were evaluated. The overall mean intra-observer agreement of CNFS grading was strong on the axial 3D T1W TSE, 3D T2W TSE, and 2D T2W TSE images for each observer with ICC values of 0.79 and 0.82. The overall mean inter-observer agreement for CNFS grading was strong on 3D T1W TSE, 3D T2W TSE, and 2D T2W TSE images with ICC values of 0.79, 0.79, and 0.86, respectively. Conclusion: Axial 3D T1W TSE, 3D T2W TSE, and 2D T2W TSE images exhibited comparable strong reliability in the grading of cervical neural foramen stenosis without the significant benefit of 3D over 2D technique.